Study of Islamic Education Policy in the Digital Era: Challenges and Opportunities for Technology-Based Learning by Utilizing Canva at SMAN 4 Kuala Nagan Raya - Mahfud, Aris; Silahuddin, Silahuddin; Agustina, Restika; Maulidia, Maulidia (Jurnal Kependidikan Media, 2025)
This study examines the implementation of technology-based Islamic education policies at SMAN 4 Kuala Nagan Raya, focusing on the challenges and opportunities in utilizing Canva as a learning medium. The research method uses a qualitative approach with data collection techniques through interviews, observations, and document analysis. The results of the study reveal three main findings: Limited infrastructure, such as unstable internet access and a lack of digital devices, hinder the optimization of technology-based learning; Low digital competence of teachers in using Canva and other educational platforms due to lack of training; Student behavior that is not yet fully adaptive to digital learning, indicated by the dominance of gadget use for entertainment rather than learning. However, this study also identifies opportunities for development, such as the enthusiasm of young teachers for technological innovation and the potential for collaboration with digital service providers. Further analysis shows the gap between national policies (such as Merdeka Belajar) and implementation at the local level, which requires a context-based approach and ongoing support. The implications of this study emphasize the importance of improving infrastructure, practical teacher training, and cultivating digital literacy to encourage effective transformation of Islamic education in the digital era.